2017
DOI: 10.4102/pythagoras.v38i1.355
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative literacy of South African school-leavers who qualify for higher education

Abstract: There is an articulation gap for many students between the literacy practices developed at school and those demanded by higher education. While the school sector is often well attuned to the school-leaving assessments, it may not be as aware of the implicit quantitative literacy (QL) demands placed on students in higher education. The National Benchmark Test (NBT) in QL provides diagnostic information to inform teaching and learning. The performance of a large sample of school-leavers who wrote the NBT QL test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In a study of the relationship between the NBT QL scores and the NSC Mathematics results of 6,271 students, the correlation coefficient was 0.63, indicating a fair degree of convergent validity (Prince and Frith 2017). In a similar study of the results of 56,662 students, the correlation coefficient was 0.58, which while still indicating some convergence, is closer to the cut-off value of r = 0.5 used in Prince (2017).…”
Section: Validity and Reliability Of The Nbt Ql Testmentioning
confidence: 53%
See 3 more Smart Citations
“…In a study of the relationship between the NBT QL scores and the NSC Mathematics results of 6,271 students, the correlation coefficient was 0.63, indicating a fair degree of convergent validity (Prince and Frith 2017). In a similar study of the results of 56,662 students, the correlation coefficient was 0.58, which while still indicating some convergence, is closer to the cut-off value of r = 0.5 used in Prince (2017).…”
Section: Validity and Reliability Of The Nbt Ql Testmentioning
confidence: 53%
“…For example, comparing the results for a large sample of test-takers revealed that in general the NBTP QL scores were about 9 percentage points lower than the NSC Mathematics scores and the NBT QL scores were about 27 percentage points lower than the NSC Mathematical Literacy results. Less than 50% of those who scored at the highest level for NSC Mathematics and less than 5% of those who scored at the highest level for NSC Mathematical Literacy obtained scores classified as Proficient in the NBTP QL test (Prince and Frith 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been acknowledged that there are significant differences between schooling in the Further Education and Training (FET) phase and higher education in South Africa -a so-called "articulation gap" -which is "manifested in students as a lack of sound foundations for tertiary studies and has a profound effect on students' ability to respond positively to higher education programmes" (Scott, Yeld and Hendry 2007, 42). Research studies have shown that one of the most important aspects of the articulation gap is the mismatch between prospective students' academic literacies and the expectations of higher education in terms of their literacy and numeracy practices (Frith and Prince 2016;Prince and Frith 2017;Cliff 2015;Weideman 2019).…”
Section: Introductionmentioning
confidence: 99%